Informovaný souhlas v gynekologii a porodnictví - Krepelka, P (Ceska gynekologie, 2006)
OBJECTIVE: A systematic review of recent available literature on the topic of informed consent, evaluation of the terminus a quo and the creation of theoretical basis for execution of the process of informed consent in clinical practice with attention to specific aspects in gynecology and obstetrics. TYPE OF STUDY: Review of literature. SETTING: Mother and Child Care Institute Prague, Chair of Gynecology and Obstetrics, IPVZ, Prague. METHODS: Review of publications on the given topic and implementation of general principles of medical ethics in the area of gynecology and obstetrics. RESULTS: The branch of gynecology and obstetrics brings about various controversial clinical situations, which arise from specific features of the branch. The informed consent is an integral part of the diagnostic-therapeutic process and precondition of the correct (lege artis) procedure. The adequate agreement with the therapy should be informed, free and competent. It prevents ethical crisis in conditions of an ethical conflict. The paper defines the content and structure of the informed consent and draws attention to its technical prerequisites so as to fulfill the truthfulness and legal validity. CONCLUSION: The informed consent is an important part of communication between the physician and the patient. The physician provides a complex, qualified, truthful and complete information. A competent patient accepts this kind of information and decides, based on full understanding, when and in what form, undergoes the recommended procedure or refuses it.
Keywords: Conflict of Interest; porodnictví; Gynecology; záznamy jako téma; Obstetrics; gynekologie; Informed Consent; střet zájmů; Records; Humans; lidé; informovaný souhlas pacienta